Pengaruh Pengumuman Boikot oleh MUI Terhadap Abnormal Return Saham Perusahaan yang Terdaftar di Bursa Efek Indonesia - Ade Muthia Afifah; M. Muhayin A. Sidik; Endang Asliana (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The boycott of products from companies suspected of being affiliated with Israel in Indonesia began with an announcement from the Indonesian Ulema Council (MUI) on Wednesday, November 8, 2023. The purpose of this research is to find out how the boycott declaration affected unusual returns. An event study approach, including an estimating period and an event observation period, is used in the research. The paired sample t-test and the one-sample Kolmogorov-Smirnov test are the tools made use of. According to the findings, the MUI announcement had no discernible effect on anomalous returns either before or after it was made public.